Penentuan Parameter Pemodelan Kecepatan Putar Motor Induksi 3 Phasa Menggunakan Jaringan Saraf Tiruan (JST) - Hatma Rudito (Politeknik Negeri Ujung Pandang, 2009)
Modeling speed control of induction machines 3 phase is very necessary, because will be make it more easier for used in mathematic analysis. In this book simulating modeling parameters is purposing give solution for made mode speed control induction machine 3 phase. And analysis using Universal Field Oriented (UFO) and Direct Field Oriented (DFO). Speed control machine 3 phase can be adapted with changing of load, so that using Neural Network. Result from analysis in this paper to give parameters mode adaptive control system in diagram block type.